2018
DOI: 10.1111/chd.12625
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma and paraganglioma in Fontan patients: Common more than expected

Abstract: Phechromocytoma/paraganglioma could occur in Fontan patients more than expected. Because it is curable by tumor resection during its early phase, early diagnosis and treatment of pheochromocytoma are crucial in Fontan patients not to make hemodynamic deterioration and aggravation of heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…They developed gastrointestinal and pancreatic neuroendocrine tumors (NETs), the first to our knowledge. These cases now join the other NETs, pheochromocytomas and paragangliomas, previously reported in this patient population [5] .…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…They developed gastrointestinal and pancreatic neuroendocrine tumors (NETs), the first to our knowledge. These cases now join the other NETs, pheochromocytomas and paragangliomas, previously reported in this patient population [5] .…”
Section: Introductionsupporting
confidence: 84%
“…This series included 5 cases and 2 of these patients were children [6] . In a more recent study of 283 Fontan patients, Song, et al, reported 3 cases of pheochromocytomas and 4 paragangliomas with 3 of the 7 patients 18 years of age or younger [5] . Three of these patients were clinically asymptomatic, while 4 had symptoms such as hypertension, headache and palpitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coexistence of CHD and P-PGL has already been reported in previous studies and a causal link between the two conditions has been postulated [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 82%
“…However, 3 of those 21 (14%) patients had a history of a cyanotic heart disease, which was unlikely to be an incidental occurrence [9]. A recent study from Korea showed that the incidence of PPGL among Fontan patients older than 10 years of age was 2.5%, which is almost fourfold higher than the general population [10]. The age of onset in these patients was also significantly earlier compared with those with no history of congenital heart disease (CHD).…”
Section: Prevalence Of Ppgl In Patients With Cchdmentioning
confidence: 99%